2019
DOI: 10.3390/nu11102310
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Diurnal Oscillatory Rhythms in Gut Microbiota Correlates with Changes in Circulating Metabolites in Type 2 Diabetic db/db Mice

Abstract: Our hypothesis is that diabetes leads to loss of diurnal oscillatory rhythms in gut microbiota altering circulating metabolites. We performed an observational study where we compared diurnal changes of the gut microbiota with temporal changes of plasma metabolites. Metadata analysis from bacterial DNA from fecal pellets collected from 10-month old control (db/m) and type 2 diabetic (db/db) mice every 4 h for a 24-h period was used for prediction analysis. Blood plasma was collected at a day and night time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 47 publications
(78 reference statements)
0
33
0
1
Order By: Relevance
“…Because the gastrointestinal microbiome modulator improved gastrointestinal intolerance in human patients treated with metformin, the modification of enterobacterial flora has been proposed to be a cause of the gastrointestinal intolerance 14. In addition, in mice, the genetic background, including obesity and diabetic phenotypes (such as db/db mice), and metformin treatment are known to induce the modification of enterobacterial flora 15–18. Therefore, we examined the differences in enterobacterial flora in metformin-induced diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Because the gastrointestinal microbiome modulator improved gastrointestinal intolerance in human patients treated with metformin, the modification of enterobacterial flora has been proposed to be a cause of the gastrointestinal intolerance 14. In addition, in mice, the genetic background, including obesity and diabetic phenotypes (such as db/db mice), and metformin treatment are known to induce the modification of enterobacterial flora 15–18. Therefore, we examined the differences in enterobacterial flora in metformin-induced diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple experimental and clinical studies have pointed out that changes in gut microbiome composition contribute to the progression of metabolic and neurodegeneration diseases via altered microbial metabolites, immune activation, and bacterial amyloids [ 54 , 55 , 56 , 57 ]. The role of the gut microbiome in neurodegenerative diseases is beginning to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Work showed that intermittent fasting altered the gut microbiome in the db/db mice, which was associated with less retinal damage [4]. Additional studies also showed that diabetes in the db/db mice led to reduced diurnal oscillatory rhythms, which altered metabolic pathways [5]. Other groups reported increased permeability and inflammatory mediators in the retina of db/db mice, which was reduced by C1q/tumor necrosis factor (TNF) related protein 9 [6].…”
mentioning
confidence: 99%